Increasing Students' Interest in Learning by Using the Discovery Learning Learning Model Assisted by Audio Visual Media at SMAN 1 Sungai Limau - Rianto, Slamet; Setriani, Loli; Despica, Rika (Asian Journal of Community Services, 2024)
This program at SMAN 1 Sungai Limau uses the discovery learning learning model with audio-visual aids to increase students' interest in learning. Information and communication technology (ICT) has advanced so quickly, and it has benefited a wide range of human endeavors. The educational sector can benefit from the advancements in information and communication technology, as there are numerous learning opportunities that arise from its application. Technology of information and communication in education will be useful as a storehouse of knowledge, learning properties, and educational tools and as a learning medium. Likewise, research and development products carried out by the Teachers in the PGRI West Sumatra University Geography Education Study Program can optimize the design of learning media by creating educational materials that will increase students' interest in learning and comprehension of the information they are absorbing in class, thereby meeting learning objectives and outcomes.